Implementasi Modul Ajar di Sekolah SDN 1 Kereng Bangkirai Palangka Raya dalam Mata Pelajaran PAK Kelas IV SD - Royasefa Ketrin Suek; Mirna Widianti; Riri Handriani; Matius Timan Herdi Ginting (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to describe the process and results of the implementation of the teaching module "My Responsibility as a Child of God" in Christian Religious Education and Character Education learning in grade IV of SDN 1 Kereng Bangkirai Palangka Raya. This module was developed to instill the value of responsibility as a Christian character in students through active learning activities that include discussions, Responsible Action Challenge games, and the preparation of personal commitments. The study used a descriptive qualitative approach with 10 students as subjects. Data were obtained through observation, cognitive, affective, psychomotor assessments, and documentation during the learning process. The results showed that students were able to understand the concept of responsibility biblically through the story of Joseph in Genesis 37–50, and showed increased enthusiasm, cooperation, and courage in expressing opinions. The personal commitment products produced by students showed that most students were able to formulate concrete actions as a form of implementation of responsibility in everyday life. Obstacles found were variations in students' ability to focus and differences in the speed of students in understanding instructions, but these could be overcome through more intensive guidance and direction.